Brazilian academic production on management control: mapping and Network Analysis (Research, Society and Development, 2020)
This study is based on the analysis of the publications of articles that deal with the management control issue in the Scientific Periodicals Eletronic Library (SPELL) indexing system and in the Annals of the Congresses of the National Association of Graduate Studies and Research in Administration (ANPAD), in function of the amplification on the current state of research in said field, as well as on the network of authors that interact and act in all its scope. Thus, it aims to achieve understanding about the development of research in the area of Management Control, and expand the knowledge about its network of authors. In this context, Social Network Analysis was used to detail the interactions and determine the protagonisms within the field of study. The main results highlight an erratic trend of growth of the area, although with sharp growth in recent years. In addition, there is evidence that the authors' profile is varied and the level of involvement irregular. The study recommends deepening and new surveys on research groups, and the level of institutional involvement with the themes.